2002
DOI: 10.1089/10849780252824055
|View full text |Cite
|
Sign up to set email alerts
|

The Experimental Research of R-Phycoerythrin Subunits on Cancer Treatment: A New Photosensitizer in PDT

Abstract: The mouse tumor cell S180 and human liver carcinoma cell SMC 7721 cells were first treated with R-PE and its subunits (alpha, beta, gamma subunits), then irradiated with Argon laser (496 nm, 28.8 J/cm2). Survival rate was measured by MTT method. In order to compare the phototoxicity in normal cells, the mouse marrow cells were treated with photofrin II and beta-subunit, irradiated with 45 J/cm2 of light; survival rate was also measured by MTT method. The result showed that R-PE subunits had better PDT effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Functional food substances from marine sources are not only pharmacologically effective but also antagonize dysregulated targets in cellular signaling pathways to exert their antineoplastic activities (Tarapore, Siddiqui, & Mukhtar, ). Phycobiliproteins are an important group of water soluble natural pigment molecules extracted from the red and blue green algae and they are nontoxic proteins with potent anticancer, antioxidant, and anti‐inflammatory properties (Bei, Guang‐Ce, Chen‐Kui, & Zhen‐gang, ; Ravi, et al, ; Senthilkumar, Kurinjimalar, et al, ; Thangam, et al, ). Hence, an investigation was carried out to evaluate the anticancer potential of RPERPE obtained from P. hornemannii (Lyngbye) Silva against HCC using male Wistar albino rats as models.…”
Section: Discussionmentioning
confidence: 99%
“…Functional food substances from marine sources are not only pharmacologically effective but also antagonize dysregulated targets in cellular signaling pathways to exert their antineoplastic activities (Tarapore, Siddiqui, & Mukhtar, ). Phycobiliproteins are an important group of water soluble natural pigment molecules extracted from the red and blue green algae and they are nontoxic proteins with potent anticancer, antioxidant, and anti‐inflammatory properties (Bei, Guang‐Ce, Chen‐Kui, & Zhen‐gang, ; Ravi, et al, ; Senthilkumar, Kurinjimalar, et al, ; Thangam, et al, ). Hence, an investigation was carried out to evaluate the anticancer potential of RPERPE obtained from P. hornemannii (Lyngbye) Silva against HCC using male Wistar albino rats as models.…”
Section: Discussionmentioning
confidence: 99%
“…They have been used as photosensitizers for the treatment of tumors (Huang et al 2002;Li et al 2000). Recent studies have also shown their applicability in immunomodulation (Román et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…APC, at nontoxic concentration to the host cells (0.045 ± 0.012 μmol/L), was found to inhibit enterovirus 71 induced cytopathic effects, viral plaque formation, and apoptosis [60] . Bei et al [61] (2002) found the role of PE in improving the selectivity of photodynamic therapy treatment of mouse tumor cells S180 and human liver carcinoma cells SMC 7721. Sonani et al [43,62] (2014a, 2014b) has recently reported the antioxidant based antiaging activity and antiAlzheimeric potential of PE (isolated from Lyngbya sp.…”
Section: Pharmaceutical and Neutraceuticalmentioning
confidence: 99%